Efecto de horas de incubación en el desempeño productivo del pollito bebe cobb 500 - Zambrano Mejía, Wilfrido Leonel (2019)
In order to evaluate the effect of incubation hours (HI) on the productive performance of the COBB 500 baby chick, four treatments were used: group of chicks born at 480, 490 and 504 hours (h) plus a control group with chicks of different born hours. A Completely Random Design (DCA) was applied. The variables were measured: weight of the yolk sac (PSV), accumulated weekly weight of chickens (PSA), daily weight gain (GDP), cumulative weekly feed consumption (CASA), cumulative feed conversion (CAA), mortality (M), adjusted conversion (CA), productive index (IP), cost benefit analysis (C / B), the results obtained in the PSV was p> 0.05 at 480 h on day two, but the GDP of 72.1g was presented in the control group, while the rest of the treatments ranged from 66.31 to 69.78 g. The HI was highly significant PSA in the different weeks. The variables CASA and CAA were not affected by the HI (p> 0.05). The lowest IP was obtained by the treatment corresponding to 504 h with 365.86 points, but the control treatment obtained 450.59, the best IP; the C / B had a superior control. It is concluded that the different incubation hours do not affect the productive performance in COOB 500 broilers.